Risk Management Analysis Based on ISO 13000 at NC University - Minarni Anaci Dethan; Yohanes Demu; Sarinah Joyce Margaret Rafael (Eduvest - Journal of Universal Studies, 2022)
In order to improve organizational governance, universities are required to carry out risk management. This study aims to help NC University to identify, analyze, evaluate and treat risks systematically. This research is a qualitative research. The data were analyzed descriptively based on the ISO 31000:2018 risk management framework, namely a risk assessment which includes identification, analysis and evaluation of risks as well as risk treatment. The result of this research is that there are risks that have been identified based on three categories, namely strategic risk, operational risk, and financial risk. In addition, there are several risk treatment actions taken.